Comparison of perioperative outcomes between open and minimally invasive esophagectomy for esophageal cancer. Issue 3 (May 2015) - Mao, Teng; Fang, Wentao; Gu, Zhitao; Guo, Xufeng; Ji, Chunyu; Chen, Wenhu
Abstract: Background: To compare surgical outcomes of thoracoscopic and laparoscopic esophagectomy with open esophagectomy in order to study the learning curve of minimally invasive surgery for esophageal cancers. Methods: Among 109 esophageal cancer patients retrospectively studied, 59 patients underwent minimally invasive esophagectomy (MIE) and 50 underwent open surgery (OE). In the MIE group, the first 30 patients received hybrid procedures, including 16 thoracoscopic esophagectomies and 14 laparoscopic maneuvers. The later 29 patients received thoraco‐laparoscopic esophagectomy (TLE). Results: The overall morbidity of MIE and OE was 42.4% (25/59) and 44.0% (22/50), respectively, with no statistical difference. However, the MIE group had a significantly lower incidence of functional complication (1.79%, 1/59) than the OE group (32.0%, 16/50, P < 0.01). The technical complication rate was not significantly different between the two groups (14/59, 23.7% vs. 6/50, 12.0%, P = NS), nor was the overall complication rate between the 30 early period cases and the 29 later cases ( P = NS); although the later cases had TLE and there was no recurrent laryngeal nerve injury. Conclusion: Minimally invasive approaches may help to decrease the risk of functional complication but not technical problems, after esophagectomy. For esophageal cancer patients to benefit from this minimally invasive surgery, an extended learning curve is necessary to avoid technical problems, such as anastomotic leakage and recurrent laryngeal nerve palsy.